Small airway dysfunction as predictor and marker for clinical response to biological therapy in severe eosinophilic asthma: a longitudinal observational study - Abdo, Mustafa; Watz, Henrik; Veith, Vera; Kirsten, Anne-Marie; Biller, Heike; Pedersen, Frauke; Mutius, Erika von; Kopp, Matthias; Hansen, Gesine; Waschki, Benjamin; Rabe, Klaus F.; Trinkmann, Frederik; et al. (Respiratory research, 2020)
Anti-T2 biological therapies have proven to effectively reduce acute exacerbations and daily doses of oral steroids in severe eosinophilic asthma. Despite the remarkable clinical efficacy, there are usually only moderate improvements in airflow limitation, suggesting that other measures of lung function like small airway dysfunction (SAD) might better reflect the clinical response. We aimed to investigate if measures of small airway function would predict and correlate with the clinical response to anti-T2 therapy.
Gesehen am 26.11.2020